2013
DOI: 10.1038/mt.2013.141
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid/Microglial Driven Autologous Hematopoietic Stem Cell Gene Therapy Corrects a Neuronopathic Lysosomal Disease

Abstract: Mucopolysaccharidosis type IIIA (MPSIIIA) is a lysosomal storage disorder caused by mutations in N-sulfoglucosamine sulfohydrolase (SGSH), resulting in heparan sulfate (HS) accumulation and progressive neurodegeneration. There are no treatments. We previously demonstrated improved neuropathology in MPSIIIA mice using lentiviral vectors (LVs) overexpressing SGSH in wild-type (WT) hematopoietic stem cell (HSC) transplants (HSCTs), achieved via donor monocyte/microglial engraftment in the brain. However, neurolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(131 citation statements)
references
References 48 publications
4
127
0
Order By: Relevance
“…Subsequent studies using more effi cient lentiviral-based vectors that transduced a greater number of the donor hematopoietic stem cells and that resulted in the secretion of higher levels of the enzyme (i.e., arylsulfatase A) completely prevented the development of neuropathology and behavioral abnormalities in mice ( 141,151 ). Similar encouraging results were obtained in mouse models of other LSDs including MPS I, MPS IIIA, globoid cell leukodystrophy, and GM1 gangliosidosis ( 142,(152)(153)(154)(155). In addition to the correction of the neurological disease, transplantation of gene-modifi ed donor cells also provided an additional benefi t of addressing the visceral components of the disease.…”
Section: Effi Cacy Of Intracranial Delivery Of Aav Vectors For Neuropsupporting
confidence: 65%
See 1 more Smart Citation
“…Subsequent studies using more effi cient lentiviral-based vectors that transduced a greater number of the donor hematopoietic stem cells and that resulted in the secretion of higher levels of the enzyme (i.e., arylsulfatase A) completely prevented the development of neuropathology and behavioral abnormalities in mice ( 141,151 ). Similar encouraging results were obtained in mouse models of other LSDs including MPS I, MPS IIIA, globoid cell leukodystrophy, and GM1 gangliosidosis ( 142,(152)(153)(154)(155). In addition to the correction of the neurological disease, transplantation of gene-modifi ed donor cells also provided an additional benefi t of addressing the visceral components of the disease.…”
Section: Effi Cacy Of Intracranial Delivery Of Aav Vectors For Neuropsupporting
confidence: 65%
“…In general, more favorable biochemical and clinical outcomes in the mice were obtained using donor cells that had been engineered to express higher levels of the respective lysosomal enzymes. For example, in the study using MPS IIIA mice, the utilization of a strong, myeloid-restricted promoter to enhance transgene expression by microglia in the CNS was necessary for robust effi cacy ( 155 ). For LSDs that are primarily characterized by neurological disease, restriction of the expression to the brain using selective promoters may be further minimized by favoring AAV serotypes that demonstrate a higher tropism for neural cells or a propensity to undergo axonal transport (e.g., AAV1, -5, -9, and -rh.10), Finally, these strategies may also be combined with the use of convection-enhanced delivery to further physically disseminate the vectors ( 114,128 ).…”
Section: Effi Cacy Of Intracranial Delivery Of Aav Vectors For Neuropmentioning
confidence: 99%
“…Therefore, transduction efficacy of our vector to HSCs may be another contributing factor to relatively low IDS activity in brains of MPS II mice transplanted with IDS-overexpressing HSCs. Additionally, a previous report showed that lentiviral ex vivo gene therapy using CD11b promoter achieved high GFP expression in CD11b positive cells and more than 10% of wild-type N-sulfoglucosamine sulfohydrolase (SGSH) activity in treated MPS IIIA mice brains 42 . This method could contribute to an improvement in our results.…”
Section: Discussionmentioning
confidence: 98%
“…Stem cell implantation, combined with gene therapy, has been performed in the treatment of nonocular genetic disorders for years (Rideout et al, 2002;Hanna et al, 2007;Sergijenko et al, 2013). hESCs can be genetically manipulated to introduce a therapeutic gene, either active or awaiting later activation once the modified hESC has differentiated into the desired cell type.…”
Section: Combining Stem Cell and Gene Therapymentioning
confidence: 99%